Chapter 4 AVATAR Therapy for Refractory Auditory Hallucinations - Ward, Tom (Springer Nature, 2016)
AVATAR therapy is part of a new and exciting wave of therapies which adopt an explicitly relational and dialogic approach to working with the distressing voices. To understand the AVATAR approach, it is important to consider its position in the evolution of psychological interventions for distressing voices.